Negotiating the city: Exploring the intersecting vulnerabilities of non-national migrant mothers who sell sex in Johannesburg, South Africa. Issue 1 (2nd January 2017) - Walker, Rebecca; Vearey, Jo; Nencel, Lorraine
Abstract: This article explores the intersecting vulnerabilities of non-national migrant mothers who sell sex in Johannesburg, South Africa – one of the most unequal cities in the world. Migrants who struggle to access the benefits of the city live and work in precarious peripheral spaces where they experience intersecting vulnerabilities associated with gender norms, race, and nationality. These vulnerabilities manifest as abuse, discrimination, criminalisation, and multiple levels of structural and direct violence. Migrant women who sell sex also face stigma and moralising associated with the illegal sale of sex, being foreign, and being a single parent. Drawing on ethnographic work with non-national migrant mothers who sell sex in Johannesburg, and from ongoing work exploring research, policy and programmatic responses to migration, sex work and health, we use an analytical lens of intersectionality to explore the daily challenges associated with encountering and negotiating intersecting vulnerabilities. We consider how these vulnerabilities form entanglements (drawing on Munoz, 2016) and are (re)produced and embodied in everyday practice in the city. We explore how they shift in significance and impact depending on context and social location, and argue for a nuanced approach to understanding migration and the sale of sex that recognises these intersecting vulnerabilities – and entanglements.